2019
DOI: 10.7150/ijms.35149
|View full text |Cite
|
Sign up to set email alerts
|

Identifying circRNA-associated-ceRNA networks in retinal neovascularization in mice

Abstract: Retinal neovascularization is a complication which caused human vision loss severely. It has been shown that circular RNAs (circRNAs) play essential roles in gene regulation. However, circRNA expression profile and the underlying mechanisms in retinal neovascular diseases remain unclear. In the present study, we identified altered circRNAs in the retinas of oxygen-induced retinopathy (OIR) mouse model by microarray profiling. Microarray analysis revealed that 539 circRNAs were significantly altered in OIR reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 38 publications
(39 reference statements)
0
33
0
Order By: Relevance
“…Although the normalized data were skewed, the distributions of the log2 ratios among the six samples presented an excellent similarity after normalization, which indicated that the data could be further analyzed. The phenomenon that the normalized data were skewed (long tail above mean/median) was also demonstrated in previously published studies (58)(59)(60). It was suggested that the sampling error and selective bias are responsible for this phenomenon, and enlarging the sample sizes is an effective strategy to decrease the sampling error and selective bias.…”
Section: Discussionmentioning
confidence: 58%
“…Although the normalized data were skewed, the distributions of the log2 ratios among the six samples presented an excellent similarity after normalization, which indicated that the data could be further analyzed. The phenomenon that the normalized data were skewed (long tail above mean/median) was also demonstrated in previously published studies (58)(59)(60). It was suggested that the sampling error and selective bias are responsible for this phenomenon, and enlarging the sample sizes is an effective strategy to decrease the sampling error and selective bias.…”
Section: Discussionmentioning
confidence: 58%
“…Emerging evidences indicated that circRNAs sponged miRNAs to exert their biological functions [19][20][21], and hsa_circRNA_103809 facilitated cancer progressions by regulating miRNAs in a competing endogenous RNA (ceRNA)-dependent manner [14,[16][17][18]22]. By searching the online Pubmed database (https://pubmed.ncbi.nlm.nih.gov/), the miRNAs, including miR-101-3p [17], miR-532-3p [14], miR-4302 [18], miR-620 [22] and miR-377-3p [16], could be sponged by hsa_circRNA_103809.…”
Section: Discussionmentioning
confidence: 99%
“…According to our recent advances in circRNAs research, circRNAs exerted their biological functions and regulated genes expression through serving as RNA sponges to competitively bind to microRNAs (miRNAs) [19][20][21]. Taken hsa_circRNA_103809 as an example, previous publications indicated that hsa_circRNA_103809 sponged multiple RNAs, including miR-101-3p [17], miR-532-3p [14], miR-4302 [18], miR-620 [22] and miR-377-3p [16].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 539 circRNAs were significantly altered, and 4 altered circRNAs, mmu_circRNA_002573, mmu_ circRNA_011180, mmu_circRNA_016108 and mmu_ circRNA_22546, were validated by qRT-PCR. 123…”
Section: T a B L Ementioning
confidence: 99%
“…In addition, circRNAs were detected by microarray assay in the retinas of an OIR mouse model. A total of 539 circRNAs were significantly altered, and 4 altered circRNAs, mmu_circRNA_002573 , mmu_circRNA_011180 , mmu_circRNA_016108 and mmu_circRNA_22546 , were validated by qRT‐PCR 123 …”
Section: Circrnas In the Retinamentioning
confidence: 99%